Application of Data Visualization in Data Analysis of Inclinometer Hole. Issue 1 (July 2021) - Jie, Yang; Xiaoyan, Xu; Pengli, Zhang; Jiaming, Wang
Abstract: The deformation measurement data of the bank slope survey hole is one of the typical physical quantities characterizing the safety state of the bank slope. The measurement results of the inclinometer hole are two-way horizontal displacements perpendicular to each other at different depths, and the traditional two-dimensional analysis diagram can't show the vectorization of the horizontal displacement of the inclinometer hole well, neither highlighting the change of displacement with time nor showing the direction of displacement. In this paper, the measuring principle of inclinometer hole is introduced firstly, and then the monitoring data of several inclinometer holes on the back bank slope of an arch dam is taken as an example to visualize, and the advantages and disadvantages of traditional two-dimensional analysis chart, three-dimensional process analysis chart and spatial displacement analysis chart in visualizing the measuring results of inclinometer hole are compared and analysed. It has certain reference significance for the analysis of the monitoring results of inclinometer holes.